2019
DOI: 10.1002/oby.22649
|View full text |Cite
|
Sign up to set email alerts
|

Early Nonfood Parent‐Infant Interactions and Development of Obesity in a High‐Risk, Diverse Sample

Abstract: Objective This study aimed to understand the protective role of positive mother‐infant interactions in the context of food and nonfood behaviors against obesity risk later in life among a cohort of low‐income children at high prenatal risk due to maternal substance use during pregnancy. Methods The sample consisted of 216 mother‐infant dyads (49% boys) participating in an ongoing longitudinal study. Mother‐infant interactions during a feeding episode and a free‐play task were measured at child age 1 and 7 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…4 In a published study of a cohort of infants at high risk due to maternal substance use, Kong et al reported that warm and positive interactions between mothers and infants during play were associated with children's lower body mass index trajectories into elementary school, but quality of mother-infant interactions assessed during feeding were not associated with children's body mass index trajectories. 15 The quality of parent-child interaction in relation to child outcomes, such as obesity, has typically been assessed by coding parent and child behaviour as observed during a semi-structured play task. Yet, it is plausible that parentchild interactions differ between mealtime and playtime contexts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…4 In a published study of a cohort of infants at high risk due to maternal substance use, Kong et al reported that warm and positive interactions between mothers and infants during play were associated with children's lower body mass index trajectories into elementary school, but quality of mother-infant interactions assessed during feeding were not associated with children's body mass index trajectories. 15 The quality of parent-child interaction in relation to child outcomes, such as obesity, has typically been assessed by coding parent and child behaviour as observed during a semi-structured play task. Yet, it is plausible that parentchild interactions differ between mealtime and playtime contexts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Participating children were required to be born a singleton, be 18±2 months chronological age at study enrolment, have their gestational age available in their medical record or reported by their caregiver if not available in the medical record, live within 15…”
Section: Exclusion and Inclusion Criteriamentioning
confidence: 99%
“…They report associations with child adiposity relative to patterns of mother-child interaction and conclude that fatter children experienced less responsive interactions in each context (i.e., eating or play) (Birch et al, 1981). In a recently published study of a cohort of infants at high risk due to maternal substance use, Kong and colleagues reported that warm and positive interactions between mothers and infants during play were associated with children’s lower BMI trajectories into elementary school, but quality of mother-infant interactions assessed during feeding were not associated with children’s BMI trajectories (Kong, Eiden, & Paluch, 2019). The quality of parent-child interaction in relation to child outcomes, such as obesity, has typically been assessed by coding parent and child behavior as observed during a semi-structured play task.…”
Section: Introductionmentioning
confidence: 99%
“…En línea con esta idea, la Teoría del Apego especula que la calidad de las experiencias tempranas de los niños con sus cuidadores, determinan la regulación emocional y conductual posterior que tendrá el sujeto, incluyendo la conducta alimentaria (Kong et al, 2019). Entre los cuatro estilos de apego que diferenció Bolwby (1982), el apego inseguro parece correlacionar claramente con la obesidad, donde la inconsistencia de la figura de apego en su disponibilidad física y emocional, provoca un empobrecimiento de la regulación emocional -siendo lo opuesto al apego seguro- (Saltzman et al, 2017).…”
Section: Introductionunclassified